Tillage practices with different soil disturbance shape the rhizosphere bacterial community throughout crop growth - Wang, Ziting; Li, Yüze; Li, Tong; Zhao, Deqiang; Liao, Yuncheng (Soil & tillage research, 2020)
•Tillage selected specific rhizosphere bacterial communities during crop growth.•Different tillage practices shape the dynamics of rhizosphere bacterial communities with crop growth.•Effects of tillage as a historical event on rhizosphere bacterial community assembly. Long-term tillage practices can shape unique soil environments. The heavy disturbance caused by plow tillage can cause a series of ecological problems; thus, zero tillage is widely used as a low-disturbance conservation practice. However, it is unclear how tillage practices with different soil disturbances affect the rhizosphere microbial communities of crops during the succession of their growth stages on a background of continuous management. The rhizosphere environment may shape different microbial communities depending on the growth stage, and soil disturbance before crop planting may also have a lasting effect on the microbial community. In this study, we used 16S rRNA sequencing to analyze the assembly and composition of the rhizosphere bacterial communities of wheat at different growth stages under different tillage practices. The results showed that under different tillage practices and growth stages, the assembly and composition of the rhizosphere bacterial community changed significantly. Rhizosphere bacterial communities under the zero tillage condition appear to be more stable than those under the plow tillage condition, which may be related to the relatively low soil disturbance and unique rhizosphere environment under the zero tillage condition. In addition, our results further suggest that several soil variables may affect bacterial community assembly and composition.